MULTIDIMENSIONAL CAUSAL PATH ON ORGANIZATIONAL COMMITMENT AND JOB SATISFACTION IN INTENTION TO LEAVE BY ACCOUNTANTS - Ivan A. Setiawan; Imam Ghozali (Universitas Hayam Wuruk Perbanas, 2013)
The turnover phenomenon of professional accountants has become an important issue both amongpractitioners and academics. This study investigates the phenomenon of turnover by using constructsmultidimensional organizational commitment and job satisfaction is seen as a factor affecting theturnover, as well as using constructs of intention to leave as a proxy for turnover. Two theoreticalmodels are confirmed: Theoretical Model 1 puts multidimensional organizational commitment asantecedents to job satisfaction, and Theoretical Model 2 is the construct of job satisfaction as an antecedentto multidimensional organizational commitment. Turnover intention is the final output onboth models. This employed 107 professional accountants from various public accounting firms inIndonesia and these were analyzed by means of structural equation model (SEM). It shows that theTheoretical Model 2 is better than Theoretical Model 1. The parameter estimates indicate that a positiverelationship between job satisfaction and affective commitment. There were negative relationshipbetween job satisfaction and low alternative commitment, between job satisfaction and high sacrificecommitment, and between job satisfaction and affective commitment with intention to leave.